Empagliflozin lowers serum uric acid in chronic kidney disease: exploratory analyses from the EMPA-KIDNEY trial - Mayne, Kaitlin J.; Sardell, Rebecca J; Staplin, Natalie; Judge, Parminder K; Zhu, Doreen; Sammons, Emily; Cherney, David Z I; Green, Jennifer B; Levin, Adeera; Pontremoli, Roberto; Hauske, Sibylle J.; Emberson, Jonathan; et al. (Nephrology, dialysis, transplantation, 2025)
Hyperuricaemia and gout are common in chronic kidney disease (CKD). We aimed to assess the effects of sodium-glucose co-transporter-2 (SGLT2) inhibition on uric acid (urate) and gout in patients with CKD.The EMPA-KIDNEY trial randomised 6609 patients with CKD to receive either empagliflozin 10 mg daily or matching placebo over a median of 2 years of follow-up. Serum uric acid was measured at randomisation then at 2 and 18 months of follow-up and the effects of empagliflozin were analysed using a pre-specified mixed model repeated measures approach. Participant-reported gout events were analysed in Cox regression models (first events) with the Andersen-Gill extension (total events). A post hoc composite outcome included new initiation of uric acid-lowering therapy or colchicine. EMPA-KIDNEY primary and kidney disease progression outcomes were also assessed in subgroups of baseline serum uric acid.Baseline mean ± standard deviation serum uric acid concentration was 431 ± 114 µmol/l. Allocation to empagliflozin resulted in a study-average between-group difference in serum uric acid of −25.6 µmol/l [95% confidence interval (CI) −30.3 to −21.0], with larger effects in those with higher eGFR (trend P < .001) and without diabetes (heterogeneity P < .001). Compared with placebo, empagliflozin did not significantly reduce first or total gout events [hazard ratio 0.87 (95% CI 0.74-1.02) for the 595 first events and 0.86 (0.72-1.03) for the 869 total events] with similar hazard ratios for the post hoc composite and across subgroups, including by diabetes and eGFR. The effect of empagliflozin on the primary outcome and kidney disease progression outcomes were similar irrespective of the baseline level of uric acid.SGLT2 inhibition reduces serum uric acid in patients with CKD, with larger effects at higher eGFR and in the absence of diabetes. However, the effect on uric acid is modest and did not translate into reduced risk of gout in EMPA-KIDNEY.
Veröffentlicht: 14 September 2024
Gesehen am 11.04.2025